2018
DOI: 10.1080/0886022x.2018.1455587
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of carnitine concentration after switching from oral administration to intravenous injection in hemodialysis patients

Abstract: Carnitine has high dialyzability and is often deficient in dialysis patients. This deficiency is treated by either intravenous (IV) or oral supplementation of carnitine. In this study, the mode of carnitine administration was changed from oral to IV in 17 hemodialysis (HD) patients, and the treatment was discontinued after 1 year. We found that the levels of total carnitine (TC), free-carnitine (FC), and acyl-carnitine (AC) significantly increased after 3 months of switching to IV administration (p < .05). Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Additionally, the utility of using carnitine as an osmotic substance in PD fluid has been reported [53]. Furthermore, supplementation of carnitine by intravenous administration is more effective than oral carnitine intake in patients undergoing hemodialysis [54]. Another study showed that certain levels (80-199 lmol/L) of carnitine supplementation decreased clinical complications, such as hypotension and muscle cramps, during hemodialysis sessions compared with higher levels of free carnitine ( !…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the utility of using carnitine as an osmotic substance in PD fluid has been reported [53]. Furthermore, supplementation of carnitine by intravenous administration is more effective than oral carnitine intake in patients undergoing hemodialysis [54]. Another study showed that certain levels (80-199 lmol/L) of carnitine supplementation decreased clinical complications, such as hypotension and muscle cramps, during hemodialysis sessions compared with higher levels of free carnitine ( !…”
Section: Discussionmentioning
confidence: 99%
“…Carnitine was administered by L-Cartin FF injection 1000mg to patients three times a week in an average with Levocarnitine, which is (R)-3-Hydroxy-4-trimethylammoniobutanoate [13]. It was registered as 22400AMX01482, which has been provided for the treatment for carnitine deficiency [4]. Note: Data represent the mean value and standard error of the mean (SEM), Intervention is the adminstration of Carnitine injection for six months, dif: difference between 0 mont and 6 month, *: significant difference between 0 month and 6 month (p<0.05), np: not significant between 0 month and 6 month.…”
Section: Medical Agentsmentioning
confidence: 99%
“…Carnitine deficiency has been known in patients on Hemodialysis (HD). It has been reported that administration of carnitine may bring clinical effects, such as improving cardiac function, decreasing muscle symptoms with muscle spasm and increasing the response of EPO to anemia [4].…”
Section: Introductionmentioning
confidence: 99%